Development and Validation of a Juvenile Spondyloarthritis Disease Flare Measure: Ascertaining Flare in Patients With Inactive Disease. Issue 2 (13th September 2022) - Weiss, Pamela F.; Brandon, Timothy G.; Ryan, Meghan E.; Treemarcki, Erin B.; Armendariz, Stephanie; Wright, Tracey B.; Godiwala, Chetna; Stoll, Matthew L.; Xiao, Rui; Lovell, Daniel
Abstract : Objective: Our objective was to develop and validate a composite disease flare definition for juvenile spondyloarthritis (SpA) that would closely approximate the clinical decision made to reinitiate or not reinitiate systemic therapy after therapy de‐escalation. Methods: Retrospective chart reviews of children with SpA who underwent systemic therapy de‐escalation of biologic or conventional disease‐modifying antirheumatic drugs were used to develop and validate the flare outcome. Data on independent cohorts for development (1 center) and validation (4 centers) were collected from large tertiary health care systems. Core measure thresholds and candidate disease flare outcomes were assessed using sensitivity, specificity, positive predictive values (PPVs) and negative predictive values (NPVs), and the receiver operating characteristic (ROC) area under the curve (AUC), with physician assessment of active disease plus re‐initiation of standard dose of systemic therapy as the reference standard. Results: Of the candidate definitions, clinically meaningful worsening in ≥3 of the following 5 core measures performed best: caregiver/patient assessment of well‐being; physician assessment of disease activity; caregiver/patient assessment of pain, physical function, and active joint count. The ROC AUC was 0.91, PPV 87.5%, NPV 98.1%, sensitivity 82.4%, and specificity 98.7%. Cronbach's α was 0.81, signifying internal consistency, and factor analysis demonstrated that the outcome measured 1 construct. The Juvenile SpA Flare measure had face validity according to 21 surveyed pediatric rheumatologists. Juvenile SpA Flare had an ROC AUC of 0.85, a PPV of 92.3%, and an NPV of 96.8% in the validation cohort. Conclusion: There is initial support for the validity of the Juvenile SpA Flare measure as a tool to identify disease flare in juvenile SpA patients de‐escalating therapy, and the measure is potentially applicable in clinical practice, observational studies, and therapeutic trials.